Skin testing for immediate hypersensitivity to corticosteroids: a case series and literature review. Issue 3 (March 2015) - Baker, A.; Empson, M.; The, R.; Fitzharris, P.
Summary Background Immediate hypersensitivity to corticosteroids is reported to occur with an incidence of 0.1%. The largest previous case series reporting corticosteroid skin testing has seven patients. Methods and Patients We identified 23 patients (mean age 50 years, 65% female) from Auckland City Hospital who underwent skin testing (ST) for suspected corticosteroid hypersensitivity between July 2005 and April 2012. We performed a retrospective clinical case note review detailing clinical history of reaction, skin test results and subsequent management. Most patients (21/23) had a standard panel of testing with prednisolone, triamcinolone, methylprednisolone, hydrocortisone and dexamethasone. Skin tests used a 10% steroid stock concentration for skin prick tests (SPT) and dilutions of 1 : 1000, 1 : 100 and 1 : 10 for subsequent intradermal testing. A weal 3 mm greater than the negative control was considered positive. Results A total of 23 patients were identified who had skin testing for suspected acute hypersensitivity to corticosteroids, eight of which had a history of anaphylaxis. From 28 reactions (in 23 patients), the most common route of administration was intra‐articular (13), followed by oral (7), intravenous (3) and other (5). Skin tests were positive in 8/23 patients, and 7/8 of these patients had a history of corticosteroid‐associated anaphylaxis. Skin tests were positive at either the skin prick test or intradermal stages. There was evidence suggesting clinical and skin test cross‐reactivity between corticosteroids in one patient. One patient had a positive skin test, but negative oral challenge suggesting the skin test was false positive. Skin tests were negative in 15/23 patients. One patient had a negative prednisolone skin test and positive unblinded oral challenge, suggesting a false‐negative skin test. Conclusions Skin testing can provide sufficient evidence to diagnose allergy in patients with a clear history of immediate hypersensitivity to corticosteroids such as anaphylaxis. Both skin prick and intradermal tests should be used. There is evidence of cross‐reactivity between steroids, so a panel is recommended. False‐positive and false‐negative reactions do occur; however, the frequency is unknown. Challenge remains the only definitive way to demonstrate a safe alternative to use. Clinical Relevance As the largest case series described, this article provides new evidence for the interpretation of skin tests when investigating possible immediate hypersensitivity to corticosteroids.